The medaka alg2 mutant is a model for hypo-N-glycosylation-associated retinitis pigmentosa - Jakab, Sevinç; Sakson, Roman; Hoffmann, Marcus; Grote, Valerian; Beedgen, Lars; Thiel, Christian; Rapp, Erdmann; Ruppert, Thomas; Wittbrodt, Joachim; Thumberger, Thomas (bioRxiv beta, 2020)
Patients suffering from Congenital Disorders of Glycosylation (CDG) carry mutations in components of the evolutionarily highly conserved protein-glycosylation-machinery. Employing targeted genome editing, we modeled alleles in medaka fish based on a mutation described in an ALG2-index patient. The multisystemic phenotypes in our alg2 model closely resembled the patient’s syndromes. Molecularly, the mutation results in a reduction of the abundance of N-glycans without altering the profile of glycan structures in fish as well as in patient fibroblasts. This hypo-N-glycosylation impacted on protein abundance in two directions. We discovered a putative compensatory upregulation of the basic glycosylation and glycoprotein processing machinery highlighting the regulatory topology of the network. Conversely, proteins of the retinal phototransduction machinery were massively downregulated in the alg2 model. Those relate to the specific loss of rod photoreceptors that fail to be maintained in the alg2 mutants, a condition known as retinitis pigmentosa. Transient supply of human or medaka alg2 mRNA efficiently rescued the phenotypic spectrum and restored viability demonstrating that our alg2 model delivers key traits for the potential treatment of the disorder.